Targeted genome editing in vivo corrects a Dmd duplication restoring wild‐type dystrophin expression. Issue 5 (16th March 2021) - Maino, Eleonora; Wojtal, Daria; Evagelou, Sonia L; Farheen, Aiman; Wong, Tatianna W Y; Lindsay, Kyle; Scott, Ori; Rizvi, Samar Z; Hyatt, Elzbieta; Rok, Matthew; Visuvanathan, Shagana; Chiodo, Amanda; et al.
Abstract: Tandem duplication mutations are increasingly found to be the direct cause of many rare heritable diseases, accounting for up to 10% of cases. Unfortunately, animal models recapitulating such mutations are scarce, limiting our ability to study them and develop genome editing therapies. Here, we describe the generation of a novel duplication mouse model, harboring a multi‐exonic tandem duplication in the Dmd gene which recapitulates a human mutation. Duplication correction of this mouse was achieved by implementing a single‐guide RNA (sgRNA) CRISPR/Cas9 approach. This strategy precisely removed a duplication mutation in vivo, restored full‐length dystrophin expression, and was accompanied by improvements in both histopathological and clinical phenotypes. We conclude that CRISPR/Cas9 represents a powerful tool to accurately model and treat tandem duplication mutations. Our findings will open new avenues of research for exploring the study and therapeutics of duplication disorders. Synopsis: Currently, no curative therapies exist for disorders caused by tandem duplication mutations. To address this critical need, CRISPR/Cas9‐mediated removal of a duplication mutation was demonstrated in‐vivo, leading to substantial improvement in disease phenotype in a tandem duplication DMD mouse model. The first multi‐exonic Dmd tandem duplication mouse model (Dup18‐30) recapitulating a patient mutation was generated. An innovative single‐sgRNA/CRISPR Cas9 approach was utilized to correct the duplication mutation in vivo . Full‐length dystrophin restoration and significant improvement of dystrophic phenotype in the Dup18‐30 mouse was achieved. The study provides a promising proof‐of‐concept that can be broadly applied to other inherited disorders caused by tandem duplication mutations. Abstract : Currently, no curative therapies exist for disorders caused by tandem duplication mutations. To address this critical need, CRISPR/Cas9‐mediated removal of a duplication mutation was demonstrated in‐vivo, leading to substantial improvement in disease phenotype in a tandem duplication DMD mouse model.